Reporting of serous effusions in accordance with Indian Academy of Cytology guidelines in a tertiary care centre: a 1-year study - Gulia, Manish; Gulia, Sandhya P.; Mittal, Shivanshi S.; Rana, Surya; Tathagat; Aaryan (International Journal of Research in Medical Sciences, 2024)
Background: The objective of the present study was to categorize serous effusions in accordance with the Indian Academy of Cytology (IAC) guidelines, evaluate the characteristics of various types of serous effusions using cytological findings, and determine the risk of malignancy within different diagnostic categories. Methods: The study conducted at a tertiary care teaching hospital focused on patients with pleural, and peritoneal effusions/ascitic fluid, using retrospective data from patient records. Samples sent to the pathology department for cytopathological analysis over a one-year period after obtaining approval from institutional ethics committee (IEC). The statistical methods used included descriptive statistics and frequency analysis to examine the different cell types and characteristics present in the effusions. Risk of malignancy was calculated for each category. A Chi-square test was used to assess the relationship between different diagnostic categories, with a p value of <0.05 indicating statistical significance. Results: The findings of the study indicate that out of a total of 161 cases, there were 127 (78.88%) male patients and 34 (21.12%) female patients, resulting in a male to female ratio of 18:5. Ascitic fluid was present in 103 cases (64%) and pleural fluid in 58 cases (36%). The majority of cases, 148 (91.92%), fell into the benign category, followed by 5 cases (3.10%) in category 3, 3 cases (1.86%) in category 5, 2 cases (1.24%) in category 4, and 3 cases (1.86%) in category 1. A statistically significant p value of 0.04 was found among the different diagnostic categories. Conclusions: The IAC has specific guidelines and recommendations for reporting serous effusion cytology to ensure accurate and consistent interpretation of results. In conclusion, reporting serous effusion cytology according to IAC guidelines is essential for accurate diagnosis, prognostic information, quality assurance, communication with the healthcare team, and promoting research and education in the field. Adhering to these guidelines ensures standardized reporting practices and improves patient care outcomes.